Broader Sustainability and CSR Strategies for Stryker in Europe - Yosua Catur Satya (iBuss Management, 2022)
The medical technology industry has been growing rapidly in the last few years. With Stryker Corporation experiencing continuous growth, they become well-known for leading the medical technology industry by providing innovative products and services such as medical and surgical equipment, orthopedics, and neurotechnology. Stryker Corporation is mainly based in the United States. However, in the last decade, they have expanded globally. Stryker Corporation has a regional headquarter based in the Netherlands for managing all of its European operations. With greater operations comes greater responsibility. Stryker Corporation realized the importance of Sustainability and CSR that a company needs to have to be sustainable and positively impact its surroundings. This way, Stryker Corporation could also retain loyal customers and gain market share. Therefore, this research will deeply study the importance of sustainability and CSR, their impacts, and how best to improve Stryker’s existing sustainability and CSR programs. This report consists of Stryker Corporation’s problem analysis, current strategy regarding sustainability and CSR, customer preferences, competitive situation, and recommendations. The recommendation is completed with the strategies for how the company could improve and obtain the goals. This research was conducted by evaluating Stryker Corporation with two main methods; primary (on-site survey) and secondary research. The researcher suggests that the company could optimize and strategize clear and united sustainability and CSR programs in Europe, ensure Europewide coverage and exposure, and provide thorough sustainability and CSR reporting.Keywords: Sustainability, CSR, The 3 pillars of sustainability, ESG, Programs and initiatives